Application of the effective crack method to mode I and mode II interlaminar fracture of carbon/epoxy unidirectional laminates - Morais, A.B. de
This paper describes an experimental study involving double cantilever beam (DCB), end-notched flexure (ENF) and 4-point end-notched flexure (4ENF) tests on carbon/epoxy unidirectional specimens. The main purpose was to evaluate the so-called effective crack method (ECM), which avoids operator crack position monitoring. Extensive fibre bridging in DCB tests made the ECM inappropriate, as shown in subsequent finite element analyses. On the other hand, the ECM gave very consistent results from ENF tests, despite the usually unstable initiation. The present results confirmed some dependence of perceived initiation toughness values on ENF specimen geometry predicted in recent numerical studies. Differences between results of ENF and 4ENF tests could be explained by friction effects in the latter.